Fire Resistance of Prefabricated Steel Tubular Columns with Membrane Protections - Xinxin Zhang; Xiang Yuan Zheng; Wentao Li (Buildings)
With the acceleration of construction industrialization and carbon reduction goals, prefabricated steel structures are widely used for their efficiency and strength. However, steel’s poor fire resistance limits its use. At high temperatures, steel weakens, leading to collapse risks. Common fire protection methods like rock wool, fire-resistant boards, and coatings focus on single materials, leaving composite systems for modular steel columns understudied. This study systematically examines the fire resistance of modular steel columns with composite protective layers through tests and simulations. It finds that rock wool shrinks under heat, reducing its effectiveness by approximately 66.7%, and suggests construction improvements to mitigate this issue. A simplified fire resistance formula is proposed, showing that the total fire resistance of multi-layer systems approximates the sum of each layer’s resistance. These insights offer practical design guidance and fill a key research gap in composite fire protection for modular steel structures.